Investigation of the impact of product thickness and strain on cold forging processes - Nazal, Samya A.; Nasser, Mohamed A.; Hanon, Muammel M.; Ameen, Hani A. (Acta Polytechnica, 2024)
This study investigates the impact of sheet metal thickness and strain generated on a cold forging process. A cold forging die was manufactured based on a numerically modelled product design that considered stress concentration die profiles. Experiments involved cold forging various sheet metals (lead, brass, aluminium, and steel) with thicknesses ranging from 2mm to 6mm to assess their influence on the thickness and strain. An assumption was formulated using Solidworks to determine the appropriate sheet metal thickness based on the material type. This assumption, based on volume considerations, showed practical applicability for selecting sheet metals with thicknesses close to those designed in the numerical modelling. The results revealed that softer materials, such as lead and aluminium, closely approximated the design thickness, particularly in the central region of the die profile, with error deviations of 1.14 % and 4.36 %, respectively. In contrast, harder materials demonstrated larger deviations from the design, with minimum errors of 4.94 % for brass and 5.73 % for steel. All sheet metals underwent compressive strain in the central region of the die profile due to the stamping operation. This work demonstrates a practical approach for selecting sheet metals based on material and thickness considerations, providing insights into the behaviour of different materials during the cold forging process.